Sabang Island Tourism Services And Facilities In The Review Of Islamic Economic Perspective - Herliani Herliani; Aswin Hidaya Tarihoran (Proceeding International Seminar of Islamic Studies, 2019)
Soaktor is basically an activity tourism-related attraction and tourism support activities.The development of a tourist attraction or tourist area has a multiplier effect because it can encourage the growth of various other economic activities.Tourism in Aceh, especially along the coastal areas of the city of Sabang has quite interesting attractions, especially the beach and sea.So far in the city of Sabang there is already a marine tourism labeled Shari'ah, the tourist attractionsit is already classified as sharia tourist attractions.This research is associative, that is, research that intends to examine and measure problems with what the circumstances are so that it is only an attitude of facts.The results of this study, obtained an overview of two important indicators, namely: for services provided by tourgate consisting of women and men who make the convenience of tourists who end up doing diving and snokling activities.For facilities provided by Sabang Island tourism in the form of the availability of bathrooms, places of worship, food and homestay in accordance with Islamic Sharia, this can be seen from the availability of clean water for ablution, food that is guaranteed cleanliness and halal and there is already a separation between male homestays and women.